Adapt LLC - and Adapt LLC
Doing Development Differently… Adapt LLC provides expertise to international development practitioners seeking to improve the impacts of their investments through a more in-depth understanding of the political and economic risks and opportunities associated with programming in complex environments. The Adapt team enhances the design and implementation of international development assistance strategies, programs, and projects around the world.